Phyto-Phospholipid Conjugated Scorpion Venom Nanovesicles as Promising Carrier That Improves Efficacy of Thymoquinone against Adenocarcinoma Human Alveolar Basal Epithelial Cells - Hani Z. Asfour; Usama A. Fahmy; Waleed S. Alharbi; Alshaimaa M. Almehmady; Abdulmohsin J. Alamoudi; Singkome Tima; Rasha A. Mansouri; Ulfat M. Omar; Osama A. A. Ahmed; Shadi A. Zakai; Ahmed A. Aldarmahi; Alaa Bagalagel; et al. (MDPI AG, 2021)
Lung cancer is a dangerous type of cancer in men and the third leading cause of cancer-related death in women, behind breast and colorectal cancers. Thymoquinone (THQ), a main compound in black seed essential oils, has a variety of beneficial effects, including antiproliferative, anti-inflammatory, and antioxidant properties. On the other hand, scorpion venom peptides (SV) induce apoptosis in the cancer cells, making it a promising anticancer agent. THQ, SV, and Phospholipon® 90H (PL) were incorporated in a nano-based delivery platform to assess THQ's cellular uptake and antiproliferative efficacy against a lung cancer cell line derived from human alveolar epithelial cells (A549). Several nanovesicles were prepared and optimized using factorial experimental design. The optimized phytosome formulation contained 79.0 mg of PL and 170.0 mg of SV, with vesicle size and zeta potential of 209.9 nm and 21.1 mV, respectively. The IC50 values revealed that A549 cells were significantly more sensitive to the THQ formula than the plain formula and THQ. Cell cycle analysis revealed that THQ formula treatment resulted in significant cell cycle arrest at the S phase, increasing cell population in this phase by 22.1%. Furthermore, the THQ formula greatly increased cell apoptosis (25.17%) when compared to the untreated control (1.76%), plain formula (11.96%), or THQ alone (13.18%). The results also indicated that treatment with THQ formula significantly increased caspase-3, Bax, Bcl-2, and p53 mRNA expression compared to plain formula and THQ. In terms of the inflammatory markers, THQ formula significantly reduced the activity of TNF-α and NF-κB in comparison with the plain formula and THQ only. Overall, the findings from the study proved that a phytosome formulation of THQ could be a promising therapeutic approach for the treatment of lung adenocarcinoma.